Wykorzystywanie technologii informacyjno-komunikacyjnych (TIK) w nauczaniu zdalnym - Cimaszewska-Kuniniec, Gracja (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
Over the past few decades, ICTs have been widely used in all areas of life and business and have effectively changed the way people operate and function in the labor market. However, the integration of ICT into education is a more recent phenomenon. The underlying reasons are perhaps closely related to the pedagogical aspirations of the education system. While traditional education takes place in the form of social learning (group activities) or is entirely teacher-led, the pedagogical change brought by education based on ICT tools is a shift from teacher-centered to student-centered learning. As such, these tools empower students, make learning interactive and develop critical thinking. They also encourage and facilitate more contextualized learning processes. ICT has helped to remove the isolation associated with distance learning and has changed the nature of remote education. In this discussion, I will examine the aforementioned changes and how they have affected secondary and higher education lecturers and students who have no choice but to study at a distance and choose to use ICTs to gain flexible access to online classes and resources.